Pellet manufacturing potential of forest residuals of Cupressus lusitanica and Tectona grandis in Costa Rica - Tenorio-Monge, Carolina (2016)
The process of transformation and sawmilling of sawlog generates residuals that can be used as sources of raw material for the production of pellets. The aim of this study was to evaluate the efficiency, pellet quality for x-ray photographic and the energetic, physical and mechanical properties of pellets fabricated from residuals obtained from processing sawlogs of Cupressus lusitanica and Tectona grandis. The results showed a percentage of low efficiency for both species, 25% for C. lusitanica and 20% for T. grandis. In the quality evaluation, pellets were found that pellet fabricated with C. lusitanica pellets is characterized by having high density areas (about 1300 kg m-3) and few cracks of short size on the surface. But the pellets of T. grandis residues present an irregular density (high and low density in the pellet) and present deeper and longer cracks. Regarding the properties evaluated, it was found that the pellets of T. grandis were characterized by having a lower apparent density, lower net calorific power, lower resistance to compression and lower uniformity in the density of its surface and a greater percentage of ash, moisture content and mechanical durability, if they are compared with pellets of C. lusitanica.